Effects of Insecurity and Migration on Visual Arts Education and Entrepreneurship in Nigeria - Chinagorom C. C.; Kanu Clement Emenike (Journal of Advanced Research in Education, 2024)
Insecurity and migration have become burning issues, persistently turning into a global phenomenon. Africa is worst hit in these enduring trends, telling on the developing and underdeveloped countries. Nigeria’s situation is more dicey compared to other nations. These unfortunate situations aggravate Nigeria’s continuous loss of her labour force; technocrats and great talents who would have contributed positively to the growth and economic development of the nation, resulting in shortage of human capital. This does not augur well for the country. Some areas that will be affected if nothing seriously is done are health, education, and business sectors to mention but a few. This paper looks at insecurity and migration as factors deterring the contribution of visual arts towards growth and development of entrepreneurship in Nigerian education system. The Concepts of visual art, insecurity, migration and entrepreneurship were discussed. Data were sourced through secondary sources like newspaper publications, books, journals and internet. Findings show that insecurity is the main contributor to migration. Suggestions were proffered which include that the government should create an enabling environment where Nigerian workers find it easy to contribute effectively to the economic growth of the nation.